Analysis of Agenda Setting and Sentiment in Regional Revenue and Expenditure Budget Reporting on Kompas.Com for the 2020–2024 Period Using Computational Content Analysis - Nurdyansa, Nurdyansa; Amri, Nur Fadhila (Pusat Studi Pembangunan dan Pemberdayaan, 2024)
This study aims to analyze the pattern of reporting on the Regional Revenue and Expenditure Budget (APBD) in the online media Kompas.com during the 2020–2024 period using a computational content analysis approach. This study focuses on the distribution of intensity, sentiment tendencies, and themes and narrative constructions built by the media related to the APBD issue. Data were taken through web scraping of 590 articles containing the keyword